2015
DOI: 10.4037/ccn2015392
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Satisfaction and Compassion Fatigue Among Critical Care Nurses

Abstract: BACKGROUND Although critical care nurses gain satisfaction from providing compassionate care to patients and patients' families, the nurses are also at risk for fatigue. The balance between satisfaction and fatigue is considered professional quality of life. OBJECTIVES To establish the prevalence of compassion satisfaction and compassion fatigue in adult, pediatric, and neonatal critical care nurses and to describe potential contributing demographic, unit, and organizational characteristics. METHODS In a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
216
9
19

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(286 citation statements)
references
References 23 publications
(34 reference statements)
27
216
9
19
Order By: Relevance
“…Differences in report and variation in years where studies conducted might speculate using different criteria to investigate STS resulting in variation in reported findings. Variation among these findings implies that gender does not relate STS, but these findings must be interpreted cautiously for three reasons: majority of ED nurses are females [16], female nurses had higher level of stress than male nurses [36], and female nurses had higher level of compassion fatigue than male nurses [37]. These inconsistent findings caused Hensel et al to suggest the need for more research and further investigation to elucidate this relationship and the role of gender in STS [22].…”
Section: Personal Factorsmentioning
confidence: 80%
“…Differences in report and variation in years where studies conducted might speculate using different criteria to investigate STS resulting in variation in reported findings. Variation among these findings implies that gender does not relate STS, but these findings must be interpreted cautiously for three reasons: majority of ED nurses are females [16], female nurses had higher level of stress than male nurses [36], and female nurses had higher level of compassion fatigue than male nurses [37]. These inconsistent findings caused Hensel et al to suggest the need for more research and further investigation to elucidate this relationship and the role of gender in STS [22].…”
Section: Personal Factorsmentioning
confidence: 80%
“…24 Recently several authors have studied the related topics of futile treatment, 25 ethical situations leading to conflict, 26 and compassion fatigue and compassion satisfaction. 27,28 In their study on perceptions of nurses and physicians of futile care, Neville et al 25 found that agreement between the professions was low and providing futile treatment to patients is related to moral distress in nurses. Pavlish et al 26 evaluated an ethics screening and early intervention tool as a proactive approach to ethical conflicts, which may alleviate moral distress.…”
Section: Compassion Fatigue and Satisfactionmentioning
confidence: 99%
“…Stronger support systems and positive coworker relationships were also reported for those individuals with higher compassion satisfaction scores. Sacco et al 28 used the same tool to measure compassion fatigue, compassion satisfaction, secondary traumatic stress, and burnout in critical care nurses, in addition to focusing on organizational characteristics. There were higher levels of burnout and secondary traumatic stress among nurses who experienced a recent change in management or major system/practice change, or worked on a unit with mixed-acuity (eg, ICU/progressive care and general care) compared to single-acuity (eg, ICU only).…”
Section: Compassion Fatigue and Satisfactionmentioning
confidence: 99%
“…[22] In contrast, "compassion satisfaction is the sum of all the positive feelings a person derives from helping others". [16] The empathy that nurses provide to their patients is life giving personally and professionally. [16,[23][24][25] "Compassion satisfaction has been identified as a construct that measures these affirmative experiences".…”
Section: Compassion Fatigue and Compassion Satisfactionmentioning
confidence: 99%
“…If RNs continually neglect their own basic human needs for self-care, eventually, they will give way to symptoms of BO and TCF. [16] ". .…”
Section: Introductionmentioning
confidence: 99%